2004
DOI: 10.1021/jm040068f
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship of Heterobase-Modified 2‘-C-Methyl Ribonucleosides as Inhibitors of Hepatitis C Virus RNA Replication

Abstract: Hepatitis C virus infection constitutes a significant health problem in need of more effective therapies. We have recently identified 2'-C-methyladenosine and 2'-C-methylguanosine as potent nucleoside inhibitors of HCV RNA replication in vitro. However, both of these compounds suffered from significant limitations. 2'-C-Methyladenosine was found to be susceptible to enzymatic conversions by adenosine deaminase and purine nucleoside phosphorylase, and it displayed limited oral bioavailability in the rat. 2'-C-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(112 citation statements)
references
References 27 publications
3
108
0
1
Order By: Relevance
“…The EC 50 measured using dsRNA or capsid levels were similar, with that of the dsRNA being somewhat less, consistent with the anticipated mode of action targeting the RDRP and genome replication. Both compounds have demonstrated activity against HCV, where they target the viral RDRP by chain termination (37,38,49). By molecular modeling of the L. guyanensis LRV1 RDRP domain against other RDRPs, such as HCV, we were able to generate a view of the active site including residues putatively binding to the nucleotide substrates (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EC 50 measured using dsRNA or capsid levels were similar, with that of the dsRNA being somewhat less, consistent with the anticipated mode of action targeting the RDRP and genome replication. Both compounds have demonstrated activity against HCV, where they target the viral RDRP by chain termination (37,38,49). By molecular modeling of the L. guyanensis LRV1 RDRP domain against other RDRPs, such as HCV, we were able to generate a view of the active site including residues putatively binding to the nucleotide substrates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are now ample data suggesting that LRV1 contributes to the severity in human leishmaniasis (6,13,17,19,20,55), suggesting that anti-LRV1 inhibitors could be clinically useful, alone or in conjunction with existing antileishmanials. Unfortunately, pharmacokinetic studies of the two compounds studied here in mammals suggest that neither of these are good candidates for testing of this hypothesis just yet, as the concentration needed for LRV1 elimination (10 μM) is above the maximum achievable serum concentration in various mammalian models, typically less than 1 μM (38,49,56). Thus, future efforts must focus on the development of compounds with higher potency targeting LRV1, without significant human host toxicity.…”
Section: Antiviral Cures and The Generation Of Isogenic Lrv1mentioning
confidence: 93%
“…1, Shire, 2), the nucleoside 2-(4-amino-pyrrolo [2,3- (Fig. 1, BILN-2061, 5), were synthesized according to procedures described previously (3,6,16,30). Recombinant IFN-␣ was purchased from PBL Biomedical Laboratories, Piscataway, NJ.…”
Section: Methodsmentioning
confidence: 99%
“…These polymerase inhibitors included two nonnucleoside (thiophene amide and diamide derivatives discovered by Shire and Boehringer Ingelheim, respectively) and one nucleoside (published by Merck) inhibitors (6,16,30). The IC 50 values for Shire-thiophene amide, Boehringer Ingelheim-diamide, and Merck-nucleoside were 0.35, 1.97, and 0.27 M, respectively, which are 68-to 492-fold less potent than A-782759 (0.004 M) in this transient-transfection assay (Table 5).…”
Section: A-782759-resistant Mutants Remained Susceptible To Other Clamentioning
confidence: 99%
“…The indication was confirmed first by Yang and his co-workers using Ed4T and X-ray crystallographic method [39]. They showed that the 4'-C-ethynyl group fits into a hydrophobic MAGI = multinuclear activation of galactosesidase indicator, HIV = human immune deficiency virus, AZT = 3'-azido-3'-deoxythymidine; 3TC = 2',3'-dideoxy-3'-thia-Lcytidime; d4T = 2',3'-didehydrodideoxythymidine.…”
Section: '-C-ethynyl Group Has Special Affinity To Rtmentioning
confidence: 75%